Evaluasi Program Pemberdayaan pada Yayasan Baitul Hikmah dengan Model Context-Input-Proses-Product - Ade Salamun (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to evaluate the Development of Self-Reliance Community Program (P2KM) as corporate social responsibility that was conducted by Yayasan Baitul Hikmah PT. Elnusa Tbk by using CIPP model to know the impact of the program to the community on the periphery of the company. The program is expected that the life level of the community could be more prosperous with a commitment to a sustainable process. This research is qualitative research with a descriptive method. The results showed that the evaluation by using CIPP model showed that the program had been conducted by following concepts of community development step by step and have increased community economy-level on the periphery of the company. Moreover, the program also formed the local cadres for program sustainability that had been successful to establish a Baitul Maal wa Tamwil (BMT). The seriousness of managers and program assistants, community participation level, and community enthusiasm are supporting factors of the program. Meanwhile, the inhibiting factors are the cooperation with local authorities and related agencies that have not proceeded smoothly and the educational background of the program managers.